Quality Assurance and Foreign Languages - Reflecting on oral assessment practices in two University Spanish Language Programs in Australia - Díaz, Adriana; Hortiguera, Hugo; Espinoza Vera, Marcia (Journal of University Teaching and Learning Practice, 2015)
In the era of quality assurance (QA), close scrutiny of assessment practices has been intensified worldwide across the board. However, in the Australian context, trends in QA efforts have not reached the field of modern/foreign languages. This has largely resulted in leaving the establishment of language proficiency benchmarking up to individual institutions and programs of study. This paper discusses the findings of a cross-institutional collaborative research project focused on the comparative analysis and review of assessment practices in the Spanish language majors at the University of Queensland (UQ) and Griffith University (GU), both members of the Brisbane Universities Languages Alliance (BULA). The project had a two-pronged focus; on the one hand, establishing comparable student academic achievement standards, specifically for oral assessment in intermediate level courses; and, on the other hand, providing tools and resources to train teachers (continuing and sessional staff) in consensus moderation (CM) practices through an online platform. The results presented here offer practical pedagogical suggestions to support planning and review of oral assessment, thus contributing to QA management in languages other than English.